Hubungan Kadar Glukosa Darah dan Glukosa Urin dengan Terjadinya Infeksi Saluran Kemih (ISK) Dengan Menggunakan Media Alternatif Pada Penderita Diabetes Melitus di UPTD Diabetes Center Kota Ternate - Erpi Nurdin; Nikma Nikma; Dwiana Marta Risfiantika (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Blood glucose and urine glucose levels will increase in a history of diabetes mellitus, the accumulation of glucose in the urine is a medium for microbes to multiply, which can cause urinary tract infections in patients with diabetes mellitus. Alternative media of tuna extract agar, able to grow bacteria on gram positive and negative bacteria isolates. The aim is to determine the relationship between blood glucose and urine glucose levels on UTI-causing bacterial cultures in urine using tuna alternative media. The research method is descriptive with a comparative approach. Based on the research that has been carried out, the results are described that identified 100% increased blood glucose levels, 63 respondents with high blood glucose levels accompanied by positive results of urine culture on alternative media, and there were 29 respondents with positive urine glucose levels accompanied by positive results of bacterial culture causes of UTI in urine. The conclusion is that an increase in blood and urine glucose can lead to urinary tract infections, even though they are very weak. The p value is 0.036 which states that the correlation between blood glucose levels and the results of UTI-causing bacteria culture in urine using alternative media, namely the strength of the correlation is very weak (0.0 - <0.2). The p value is 0.014 which states that the correlation between urine glucose levels and urine culture results using alternative media, namely the strength of the correlation is very weak (0.0 - <0.2).